1987
DOI: 10.1190/1.1442302
|View full text |Cite
|
Sign up to set email alerts
|

Full transmitter waveform transient electromagnetic modeling and inversion for soundings over coal measures

Abstract: Modeling of transient electromagnetic soundings requires consideration of the full bipolar transmitter waveform in order to obtain full measurement accuracy from field instruments, The full-waveform transient may be computed using existing impulse-response forward algorithms followed by a convolution procedure with truncation and residual estimation after an even number of terms, which results in average increases in run time of about 80 percent.Simple calculations based on approximations for the behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 16 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…Attention has been paid mainly to investigations of the dependence of high conducting target signal on the width of the transmitter pulse (e.g., Smith, 1998;Liu, 1998). A phenomenon similar to the frequency dependence was discussed by Asten (1987) based on a full transmitter waveform consideration. It was shown that the effect of the repetitive transmitter waveform is severe on coil recordings over highly conductive ground.…”
Section: Field Trialsmentioning
confidence: 99%
“…Attention has been paid mainly to investigations of the dependence of high conducting target signal on the width of the transmitter pulse (e.g., Smith, 1998;Liu, 1998). A phenomenon similar to the frequency dependence was discussed by Asten (1987) based on a full transmitter waveform consideration. It was shown that the effect of the repetitive transmitter waveform is severe on coil recordings over highly conductive ground.…”
Section: Field Trialsmentioning
confidence: 99%
“…In addition to the subsurface resistivities the earth response depends on the transmitter waveform. Asten (1987) shows that modeling of the full transmitter waveform is crucial to the inversion result. In the subsequent equations, B denotes magnetic field.…”
Section: Lp Filters In the Forward Responsesmentioning
confidence: 99%
“…sometimes assumed to be identical to that obtained from a step function, but corrections for repetitive waveform are now routinely applied (e.g., ASTEN, 1987). The repeated pulses allow coherent stacking of repeated transients, thus reducing noise levels.…”
Section: Depth Of Investigation Of Pulsed Sourcesmentioning
confidence: 99%